GENDER PERFORMATIVITY IN THE FILM “TRUE SPIRIT” BY SARAH SPILLANE - Djailani, Sriwahyu Prasetyo; Husain, Dahlia; Mariana, Ana (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
This research examines  the  gender  performativity  displayed  by  the  female  main character in the film "True Spirit" using qualitative methods and Judith Butler's theory. The data collection technique was carried out through taking documentation of pieces of images that showed the existence of gender pervormativity from the movie scene. The data analysis technique used is the Miles & Huberman analysis model, namely data reduction, data display, and conclusion drawing. The results of this study to find out the self of gender identity in this study can be seen through: performative Appearance  and  physical,  and  performative  environment.  Appearance and physical performative consists of 14 data and performative environment consists of 11 data. In conclusion, the film "True Spirit" by Sarah Spillane shows the existence of gender pervormativity produced through actions and also the role of the social environment displayed by the main character in this film. As a suggestion, this research is expected to be an additional information and reference for other researchers who are interested in researching and also developing gender performativity studies in films. This research provides an overview of how performativity shapes one's self-identity.